2019
DOI: 10.1111/1755-6724.14029
|View full text |Cite
|
Sign up to set email alerts
|

Microearthquakes preceding a M4.2 Earthquake Offshore Istanbul

Abstract: A primary hurdle in observing small foreshocks is the detection-limit of most seismic networks, which is typically about magnitude M1-1.5. We show that a start-up test of a borehole-based seismic network with a much lower detection limit overcame this problem for an M w 4.2 earthquake. This earthquake occurred offshore of Istanbul, Turkey, on a fault system that is likely to rupture in an M > 7 event in the coming decades. In the three days before and two after, a total of 62 or more earthquakes, including at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Retrospective studies on megathrust earthquakes (e.g., Schurr et al., 2014; Socquet et al., 2017) have shown that the complex multi‐scale generation process of large earthquakes might have different dominant features (e.g., foreshocks or slow slip events and creep phenomena identifiable by geodetic measurements) depending on the tectonic environment. As a result of scientific developments in infrastructures and data‐mining strategies, systematic patterns in seismicity and crustal deformation preceding large earthquakes have started to emerge (Bouchon et al., 2013; Kato et al., 2012; Malin et al., 2018; Socquet et al., 2017; Yoon et al., 2019), showing that micro‐ and small‐magnitude events before large earthquakes can highlight temporal and spatial peculiar patterns in their evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective studies on megathrust earthquakes (e.g., Schurr et al., 2014; Socquet et al., 2017) have shown that the complex multi‐scale generation process of large earthquakes might have different dominant features (e.g., foreshocks or slow slip events and creep phenomena identifiable by geodetic measurements) depending on the tectonic environment. As a result of scientific developments in infrastructures and data‐mining strategies, systematic patterns in seismicity and crustal deformation preceding large earthquakes have started to emerge (Bouchon et al., 2013; Kato et al., 2012; Malin et al., 2018; Socquet et al., 2017; Yoon et al., 2019), showing that micro‐ and small‐magnitude events before large earthquakes can highlight temporal and spatial peculiar patterns in their evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Jones, 1985;Abercrombie and Mori, 1996;Reasenberg, 1999;Felzer et al, 2004;Dodge et al, 1996;Bouchon et al, 2011;Ruiz et al, 2014bRuiz et al, , 2017Ellsworth and Bulut, 2018;Yoon et al, 2019). Foreshocks are thus one of the most useful tools to understand the physics of earthquake initiation in real faults (Brune, 1979;Abercrombie and Mori, 1996;Malin et al, 2018). Therefore, it is important to improve foreshock observations and characterization, particularly for the more frequent small to moderate-sized events (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of foreshocks is today routine in laboratory experiments (Zang et al, 1998;Goebel et al, 2012;Renard et al, 2019, and references therein), while studies that focus on large earthquakes remain relatively sparse (i.e., M w >6) (e.g., Mogi, 1963;Abercrombie and Mori, 1996;Kato et al, 2012;Chen and Shearer, 2013;Bouchon et al, 2013;Ruiz et al, 2014b). However, the recent improvements to seismological monitoring systems around active faults have now provided detailed analysis of foreshocks that precede the more frequent small to moderate-sized earthquakes (M w < 6) (e.g., Savage et al, 2017;McMahon et al, 2017;Malin et al, 2018). One intriguing feature that has emerged from these more recent studies is the increased complexity (i.e., fault interactions, volumetric processes) that have been revealed through the availability of better data (e.g., near-fault receivers) and more advanced detection methods (e.g., template matching) to study foreshocks.…”
Section: Introductionmentioning
confidence: 99%
“…On June 25, 2016, a ∼50‐daylong SSE was recorded along the Çınarcık Fault below the eastern Sea of Marmara, which was interpreted as the strain release equivalent of a M w 5.8 at the depth of 9 km (Martínez‐Garzón et al., 2019). The authors assume the source location to be near to the M w 4.2 Yalova earthquake (Malin et al., 2018) that occurred during the onset of the SSE (Figure 2d), although the depth was difficult to constrain after being recorded at a single station.…”
Section: Plate Boundaries and Fault Systems In The Central‐eastern Mediterraneanmentioning
confidence: 99%